Fossil lemurs from Egypt and Kenya suggest an African origin for Madagascar’s aye-aye - Gregg F. Gunnell (Nature Portfolio, 2018)
The fossil taxon Propotto was originally identified as a primate, but is currently widely interpreted as a bat. Here, the authors identify Propotto as a stem chiromyiform lemur and, based on phylogenetic analysis, suggest two independent lemur colonizations of Madagascar.